The truth of death in the Pardoner‟s Tale. - Chee, Angeline Huijie. (2011)
The Pardoner is perhaps the most puzzling pilgrim in The Canterbury Tales, and his tale one of the most thrilling, and perhaps also the one tale to penetrate most deeply into the human psyche. This essay approaches the Pardoner with a study on trouthe and how it works in the Tale. The changing semantics of the word ‘trouthe’ and its synonyms suggests a complexity of the word that Chaucer and his contemporaries are grappling with through fiction as a medium, over the common-day legal and ethical usage of the word. What emerges from the study is the frightening truth of the double death of the body and the soul, and conversely the hope that through death in the body there is eternal life yet for the soul. It is knowledge of this, and disbelief of it that makes for the Pardoner’s deep despair. This essay takes a sympathetic reading of the Pardoner, and considers how the Tale and its study of various morals is the extension of the Pardoner’s personal obsession with the law, punishment and death. The consideration is also one of how the Pardoner’s literal-mindedness makes him unable to see the spirit of the law in the letter of the law, and his personal inability to be optimistic and hopeful despite having a desire to, as seen through the love-song that he sings in the General Prologue. The Pardoner’s Tale and Prologue is a study on the human psyche and how it responds to what is perhaps an innate and natural spirituality.